Profiles of domestic violence victims and perpetrators: a qualitative research perspective - Abdul Ghani, Mariny; Ahmad, Noor Azizah; Mohamad, A. (Akademia Baru, 2016)
Domestic violence remains a problem in the Malaysian society.The national statistics on violence against women has shown that domestic violence was recorded among the highest in the category. Domestic violence is often described as a family-centred problem and generally understood as patterns of abusive and coercive behaviour which may cause physical injuries, psychological and emotional disturbances, sexual intimidations as well as financial oppressions to the victim.In this article, the demographics of the women victims and their spouses or ex-spouses were described.All data was collected using self-reporting questionnaires which filled up by those women themselves.Profiles of the women sample (and the perpetrators) were analysed via the PASW Statistics 18 Advanced Statistical procedure.The findings obtained from the analyses are discussed in relation to the demographical characteristics of the women and their male counterparts.These basic features of the sample aim to offer a glimpse of domestic violence occurrences rather than seek to be representative to the population. The purpose of this present study is to add to the growing body of knowledge on domestic violence against women (from the qualitative research point of view) as well as to enhance the understanding on the real circumstances of the problem